Exploring Higher Education Demand and Opportunities for Young Refugees in Africa - Lawson, Late; Essah, Pauline; Samson, Krista; Welsh-Kinnersley, Michaelene (International Journal of African Higher Education, 2024)
Higher education for young people, including marginalised groups, is essential for equitable and sustainable development. There is limited research on refugees’ access to higher education, especially in developing countries. This article contributes to the literature on refugee education by raising awareness of the demand for education and issues surrounding refugees’ access to higher education in West and Central Africa (WCA). We consider changes in the population of young refugees as a proxy for shifts in their demand for education and map available opportunities and challenges. Our analysis of refugee youth demographic data indicates increasing trends in most WCA countries, signalling rapidly growing demand for (higher) education by refugees in their countries of asylum. Mapping these countries’ provision of refugee education opportunities and dedicated scholarship programmes for refugees, as well as interviews with refugee students promotes understanding of the conditions and challenges they confront in the transition to higher education in their host countries. The article highlights the urgency of the refugee situation in Africa and calls for immediate and practical action to facilitate and support refugees’ access to tertiary education.